Enantioselective total syntheses of (+)-stemofoline and three congeners based on a biogenetic hypothesis - Huang, Xiong-Zhi; Gao, Long-Hui; Huang, Pei-Qiang (Nature communications, 2020)
The powerful insecticidal and multi-drug-resistance-reversing activities displayed by the stemofoline group of alkaloids render them promising lead structures for further development as commercial agents in agriculture and medicine. However, concise, enantioselective total syntheses of stemofoline alkaloids remain a formidable challenge due to their structural complexity. We disclose herein the enantioselective total syntheses of four stemofoline alkaloids, including (+)-stemofoline, (+)-isostemofoline, (+)-stemoburkilline, and (+)-(11 S ,12 R )-dihydrostemofoline, in just 19 steps. Our strategy relies on a biogenetic hypothesis, which postulates that stemoburkilline and dihydrostemofolines are biogenetic precursors of stemofoline and isostemofoline. Other highlights of our approach are the use of Horner–Wadsworth–Emmons reaction to connect the two segments of the molecule, an improved protocol allowing gram-scale access to the tetracyclic cage-type core, and a Cu-catalyzed direct and versatile nucleophilic alkylation reaction on an anti-Bredt iminium ion. The synthetic techniques that we developed could also be extended to the preparation of other Stemona alkaloids. Stemofoline alkaloids are promising lead structures for further development in the fields of agriculture and medicine. Here, the authors report the enantioselective total syntheses of four stemofoline alkaloids in 19 steps based on a biogenetic hypothesis.